In vitro antioxidant activities of stem bark, leaves and callus extracts from Amoora rohituka - Kanthesh M Basalingappa,; Kavitha Raj V,; Avinash KO,; Kumar JR,; Murugesan Karthikeyan,; Ashok Gnanasekaran,; Chandrashekrappa GK, (International Journal of Phytomedicine, 2017)
The present work examined the in vitro antioxidant activity of sequentially extracted, solvent extracts (Petroleum ether, chloroform and Methanol) of stem bark, leaves and callus from Amoora rohituka. The antioxidative capacity of the extracts were examined by using DPPH (1,1-diphenyl,2-picryl hydrazyl), ABTS (2,2’-azinobis-3-ethyl-benzothiozoline-6-sulphonic acid) and NOS (Nitric oxide scavenging) assays by using Gallic acid as standard control. Among the tested extracts, methanol extract of stem bark showed better antioxidative capacity. The total antioxidant activity was expressed as µg equivalent of Gallic acid per gram on dry weight basis. IC50 values for methanol extract of stem bark were 7.53 µg/ml; 34.92 µg/ml and 56.31 µg/ml in ABTS, DPPH and NOS assays respectively. Whereas, leaves and callus extracts showed moderate antioxidative properties.